2014
DOI: 10.1016/j.gene.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin deficiency undermines bone load-bearing capacity through inducing iron overload

Abstract: Osteoporosis is one of the leading disorders among aged people. Bone loss results from a number of physiological alterations, such as estrogen decline and aging. Meanwhile, iron overload has been recognized as a risk factor for bone loss. Systemic iron homeostasis is fundamentally governed by the hepcidin-ferroportin regulatory axis, where hepcidin is the key regulator. Hepcidin deficiency could induce a few disorders, of which iron overload is the most representative phenotype. However, there was little inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 60 publications
4
26
0
Order By: Relevance
“…Recently in a prospective cross-sectional study on 80 patients with beta thalassemia major and intermedia, the authors found that both serum ferritin and heart iron load were negatively correlated with bone mineral density [37]. Animal models of iron overload also supported the deleterious effect of excess iron on bone mineral density [12][13][14]16,38,39].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently in a prospective cross-sectional study on 80 patients with beta thalassemia major and intermedia, the authors found that both serum ferritin and heart iron load were negatively correlated with bone mineral density [37]. Animal models of iron overload also supported the deleterious effect of excess iron on bone mineral density [12][13][14]16,38,39].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, we evaluated whether iron inhibits osteogenic mixture-induced increase of ALP activity. Osteogenic mixture consisted of dexamethasone, ascorbic acid and β-glycerolphosphate induced a marked elevation of ALP activity (4.76 ± 0.36 vs. 16.59 ± 1.69 unit/mg protein) in BMSCs. Increase of ALP activity triggered by osteogenic mixture was reduced by about 40% in the presence of iron (Fig.…”
Section: Iron Down-regulates the Expression Of Runx2 And Its Downstrementioning
confidence: 96%
See 1 more Smart Citation
“…Hepcidin has been suggested to have anti-osteoporosis effects by preventing iron overload (17), suggesting that the level of hepcidin seems to be inversed with level of iron accumulation. Sun et al (18) confirmed the in vivo use of a transgenic mouse model. In addition, the relevant studies performed concerning hepcidin in osteoporosis were either from in vitro cell culture system or in vivo animal models.…”
Section: Introductionmentioning
confidence: 93%
“…Then, in the presence of the human serum for 7-10 days, the monocytes are differentiated to the macrophages [11] . It has been already found that the hipcidin hormone inhibits iron transport out of macrophages by inducing ferroportin internalization and degradation [12,13] . So, upon overexpression of hipcidin in macrophages, these manipulated cells are able to absorb iron greater than normal level.…”
Section: Hypothesismentioning
confidence: 99%